CC-CLEAR (Colon Capsule Cleansing Assessment and Report): the novel scale to evaluate the clinical impact of bowel preparation in capsule colonoscopy – a multicentric validation study. (4th May 2022) - de Sousa Magalhães, Rui; Chálim Rebelo, Carolina; Sousa-Pinto, Bernardo; Pereira, José; Boal Carvalho, Pedro; Rosa, Bruno; Moreira, Maria J.; Duarte, Maria A.; Cotter, José
Abstract: Background: Colon Capsule Cleansing Assessment and Report (CC-CLEAR) is a novel quantitative bowel preparation scale for colon capsule. Aim: The aim of this study is to validate the association between CC-CLEAR's classification and major CC outcomes: lesion detection rate, surveillance recommendations and post-CC endoscopic treatment. Methods: Multicentric cohort of consecutive CCs. An expert's panel decided post-CC recommendations. Data included CC-CLEAR and Leighton-REX scales. Major CC outcomes were associated with the different cleansing grades. Results: From 168 CC's included, findings were reported in 123 (73.2%), 67 (54.4%) of those being colorectal polyps. CC-CLEAR influenced CC's lesion detection (OR 1.25 95% IC [1.07–1.46], p -value .004) and polyp detection rate (OR 1.22 95% IC [1.04–1.43], p -value.014). Thirty-two (19%) post-CC colonoscopies were recommended, including 22 (68.75%) with at least one polypectomy. CC-CLEAR was associated with post-CC colonoscopy treatment (OR 1.40 95% IC [1.07–1.84], p -value .015). Regarding surveillance, CC-CLEAR influenced the decision for immediate CC repetition (OR 0.21 95% IC [0.12–0.36], p -value < .001) and the recommendation for CC in 3–5 years' time (OR 1.47 95% IC [1.50–1.86], p -value < .002). The Leighton–Rex scale was not correlated with major CC outcomes. Conclusion: CC-CLEAR impacts major CC outcomes: lesion detection, surveillance recommendations and post-CC endoscopic treatment. Graphical Abstract: UF0001